Membangkitkan Nasionalisme dan Industri Kreatif: Peran Pemuda dalam Program Kampung Ecotourism Batik Sokaraja Banyumas - Fauzan, Nanda Rizki Ahmad; Nafi, Muhammad Ilman; Fatimah, Dwi; Kusuma, Bayu Mitra A (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2022)
The development of digital technology and communication often leads to disintegration in a pluralistic Indonesian society, especially in the young age group who are still in the process of finding their identity. The problem is, a survey conducted by the Association of Indonesian Internet Network Providers found that 80% of internet users in Indonesia are dominated by young people who are very vulnerable to hoax information, hate speech, and the entry of radical ideologies that often undermine nationalism attitudes. In fact, rebuilding a sense of nationalism in this era of globalization is not an easy thing. People tend to choose a new culture that is considered more practical than the local culture. Now in the field of fashion, batik is here to rebuild a sense of nationalism that is starting to fade in the midst of people's modern lifestyles. Therefore, the innovation initiated in this study is the Batik Sokaraja Ecotourism Village program which aims to raise the attitude of nationalism and the creative industry by utilizing the role of youth of productive age. This study uses a qualitative research method with a descriptive approach by referring to Megan Wood's ecotourism theory as an analytical tool. The results showed that the youths succeeded in making the Batik Sokaraja producing area to apply ecotourism principles such as protecting the surrounding environment, having minimal impact on the natural environment, according to the cultural and physical context of the local area, reducing water consumption levels, managing waste carefully, meet energy needs through passive design tools, seek collaboration with local communities, offer environmental education programs, and accommodate research. This success can trigger a sense of pride in wearing batik as a national identity and move the community's economy.